Acute pancreatitis after double cardiac valve replacement: a case report - Wafae El Amraoui; Ayoub Ettaje; Oumaima Belcadi; Salim Chajai; Yassine Elmourabit; Lalla Hasnaa Leghlimi; Lahcen Marmad; Mohamed Tribak; Fadoua Lachhab; Adil Bensouda; Said Moughil (Bulletin of the National Research Centre)
Abstract Background Acute pancreatitis following cardiac surgery is a rare complication. Early recognition of risk factors and vigilance toward initial symptoms can prevent significant morbidity and mortality. Bowel ischemia and the release of inflammatory mediators during cardiopulmonary bypass play key roles in the development of acute postoperative pancreatitis. Management is generally conservative, following the modified Atlanta 2012 criteria. This paper reviews the literature and emphasizes the importance of early investigation of abdominal pain after cardiac surgery. Case presentation We report a case of severe acute pancreatitis that developed after double valvular replacement, performed during a 3-h cardiopulmonary bypass in a patient who initially had endocarditis and underwent dialysis 3 times. Considering the risk factors, the patient was diagnosed early and managed conservatively, leading to a positive outcome. Conclusions Anesthesiologists must not disregard abdominal pain after cardiac surgery in the context of risk factors, as it may indicate gastrointestinal complications, including pancreatitis, which can be among the most dangerous complications if not treated promptly.